An Umbrella Review With Meta-Analysis of Chest Computed Tomography for Diagnosis of COVID-19: Considerations for Trauma Patient Management - Gempeler, Andrés; Griswold, Dylan P.; Rosseau, Gail; Johnson, Walter D.; Kaseje, Neema; Kolias, Angelos; Hutchinson, Peter J.; Rubiano, Andres M. (Frontiers in Medicine, 2022)
Background RT-PCR testing is the standard for diagnosis of COVID-19, although it has its suboptimal sensitivity. Chest CT has been proposed as an additional tool with diagnostic value, and several reports from primary and secondary studies that assessed its diagnostic accuracy are already available. To inform recommendations and practice regarding the use of chest CT in the trauma setting, we sought to identify, appraise, and summarise the available evidence on the diagnostic accuracy of chest CT for diagnosis of COVID-19, and its application in emergency trauma surgery patients; overcoming limitations of previous reports regarding chest CT accuracy and discussing important considerations regarding its role in this setting. Methods We conducted an umbrella review using Living Overview of Evidence platform for COVID-19, which performs regular automated searches in MEDLINE, Embase, Cochrane Central Register of Controlled Trials, and more than 30 other sources. The review was conducted following the JBI methodology for systematic reviews. The Grading of Recommendations, Assessment, Development, and Evaluation approach for grading the certainty of the evidence is reported (registered in International Prospective Register of Systematic Reviews, CRD42020198267). Results Thirty studies that fulfilled selection criteria were included; 19 primary studies provided estimates of sensitivity (0.91, 95%CI=[0.88-0.93]) and specificity (0.73, 95%CI =[0.61 ; 0.82]) of chest CT for COVID-19. No correlation was found between sensitivities and specificities (rho = 0.22 , IC95% [-0.33 ; 0.66]). Diagnostic odds ratio was estimated at: DOR=27.5, 95%CI (14.7 ; 48.5). Evidence for sensitivity estimates was graded as MODERATE, and for specificity estimates it was graded as LOW. Conclusion The value of chest CT appears to be that of an additional screening tool that can easily detect PCR false negatives, which are reportedly highly frequent. Upon the absence of PCR testing and impossibility to perform RT-PCR in trauma patients, chest CT can serve as a substitute with increased value and easy implementation.